Routine or selective carotid artery shunting for carotid endarterectomy (and different methods of monitoring in selective shunting). - Rerkasem K. (2014)
BACKGROUND: Temporary interruption of cerebral blood flow during carotid endarterectomy can be avoided by using a shunt across the clamped section of the carotid artery. This may improve outcome. This is an update of a Cochrane Review originally published in 1996 and previously updated in 2001. OBJECTIVES: To assess the effect of routine versus selective, or never, shunting during carotid endarterectomy, and to assess the best method for selecting patients for shunting. SEARCH STRATEGY: We searched the Cochrane Stroke Group Trials Register (last searched September 2008), the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library, Issue 1, 2009), MEDLINE (1966 to November 2008), EMBASE (1980 to November 2008) and Index to Scientific and Technical Proceedings (1980 to November 2008). We handsearched journals and conference proceedings, checked reference lists, and contacted experts in the field. SELECTION CRITERIA: Randomised and quasi-randomised trials of routine shunting compared with no shunting or selective shunting, and trials that compared different shunting policies in patients undergoing carotid endarterectomy. DATA COLLECTION AND ANALYSIS: Two review authors independently performed the searches and applied the inclusion criteria. We identified one new relevant randomised controlled trial. MAIN RESULTS: We included four trials in the review: three trials involving 686 patients compared routine shunting with no shunting; the other trial involving 131 patients compared shunting with a combination of electroencephalographic and carotid pressure measurement with shunting by carotid pressure measurement alone. Allocation was adequately concealed in one trial, and one trial was quasi-randomised. Analysis was by intention-to-treat where possible. For routine versus no shunting, there was no significant difference in the rate of all stroke, ipsilateral stroke or death up to 30 days after surgery, although data were limited. There was no significant difference between the risk of ipsilateral stroke in patients selected for shunting with the combination of electroencephalographic and carotid pressure assessment compared to pressure assessment alone, although again the data were limited. AUTHORS' CONCLUSIONS: This review concluded that the data available were too limited to either support or refute the use of routine or selective shunting in carotid endarterectomy. It was suggested that large scale randomised trials between routine shunting versus selective shunting were required. No one method of monitoring in selective shunting has been shown to produce better outcomes.